Optimalisasi Literasi Keuangan Islami bagi Anak Panti Asuhan Ummu Aiman - Rajmia Sulianti; Jasri, Jasri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service aims to optimize Islamic financial literacy among children at Ummu Aiman Orphanage, who are economically vulnerable and have limited access to Sharia financial education. This topic is important to equip children with the ability to manage finances according to Islamic principles from an early age. The method involves providing interactive educational materials about distinguishing needs and wants, the importance of saving, and ways to earn halal income. The results show an increased understanding of Islamic financial literacy concepts and high enthusiasm in participating in the learning process. These findings confirm that direct and interactive Islamic financial literacy education is effective in shaping financial awareness based on Sharia values. Therefore, this program significantly contributes to building the economic independence of orphanage children and can serve as a model for broader educational development.